A STUDY ON THE CONTENT AND ORGANIZATION OF THE TENTH GRADE STUDENTS’ NARRATIVE COMPOSITION IN SMAN 1 GEDEG MOJOKERTO THROUGH COLLABORATIVE LEARNING (RETAIN, 2013)
Abstrak Studi ini diarahkan pada penggambaran karangan naratif siswa kelas sepuluh dalam hal isi dan organisasi melalui pembelajaran kolaboratif. Dengan menggunakan adaptasi ESL Composition Profile yang ditulis oleh Jacobs et al (1981), studi ini menjawab pertanyaan bagaimana isi karangan naratif siswa kelas sepuluh melalui pembelajaran kolaboratif dan bagaimana organisasi karangan naratif siswa kelas sepuluh melalui pembelajaran kolaboratif. Studi ini telah dirancang sebagai penelitian kualitatif deskriptif. Subyek penelitian ini adalah para siswa kelas sepuluh SMAN 1 Gedeg Kabupaten Mojokerto, sedangkan obyek penelitiannya adalah karangan naratif siswa. Karena penelitian ini adalah studi penelitian kualitatif deskriptif, peneliti adalah instrumen kunci dari penelitian ini. Dalam mengumpulkan data, beberapa prosedur telah dilaksanakan oleh peneliti, yakni: (1) peneliti meminta karangan siswa kepada guru sebagai hasil dari proses belajar mengajar; (2) peneliti menyalin karangan siswa dan mengembalikan karangan asli kepada guru; (3) peneliti membaca semua karangan siswa dan mencoba untuk memahami karangan-karangan tersebut; (4) peneliti menganalisa karangan-karangan tersebut dalam hal/istilah isi dan organisasi mengacu pada adaptasi ESL Profil Komposisi yang ditulis oleh Jacobs et al. ( 1981). Setelah melaksanakan penelitian tersebut, peneliti menemukan hasil sebagai berikut: (1) isi dari karangan naratif siswa kelas sepuluh melalui pembelajaran kolaboratif dapat digolongkan menjadi tiga: tiga karangan tergolongkan dalam Excellent to very good level, lima karangan tergolongkan dalam good to average level, dan dua karangan tergolongkan dalam fair to poor level; dan ( 2) organisasi karangan naratif siswa kelas sepuluh melalui pembelajaran kolaboratif dapat digolongkan menjadi tiga: empat karangan tergolongkan dalam Excellent to very good level, empat karangan tergolongkan dalam good to average level, dan dua karangan tergolongkan dalam fair to poor level. Kata kunci: karangan naratif, isi dan organisasi, pembelajaran kolaboratif Abstract This study is aimed at describing the tenth grade students’ narrative composition in terms of content and organization that are taught by using collaborative learning. By using the adaptation of ESL Composition Profile written by Jacobs et al. (1981) as the standard, this study answered the questions of how the content of the tenth grade students’ narrative composition through collaborative learning is and how the organization of the tenth grade students’ narrative composition through collaborative learning is. This study was designed as descriptive qualitative research. The subjects of this study were the tenth grade students of SMAN 1 Gedeg Kabupaten Mojokerto, while the object was the students’ narrative composition. Since this research is descriptive qualitative study, the researcher is the key instrument of this study. In collecting the data, some procedures were conducted by the researcher, they are: (1) the researcher asked for the students’ composition to the teacher as the result of the learning and teaching process; (2) the researcher copied the students’ composition and gave the original back to the teacher; (3) the researcher red all of the compositions and tried to comprehend the compositions; (4) the researcher analyzes the compositions in terms of content and organization based on the adaptation of ESL Composition Profile written by Jacobs et al. (1981). After conducting the research, the researcher found the result as following: (1) the content of the tenth grade students’ narrative composition through collaborative learning was categorized into three levels: three compositions were categorized into excellent to very good level, five compositions were categorized into good to average level, and two compositions were categorized into fair to poor level; and (2) the organization of the tenth grade students’ narrative composition through collaborative learning was categorized into three levels: four compositions were categorized into excellent to very good level, four compositions were categorized into good to average level, and two compositions were categorized into fair to poor level. Keywords: Content, Organization, Narrative Composition, Collaborative Learning